(untitled) (Itinera, 2023)
In Europe the street is traditionally the place of self-representation: the “Strada Nuova” in Genova has been designed in 1550 to allow noble families to build their own palaces in a competition of beauty, richness and power. In the American tradition the street became overall a place dominated by its market role (Venturi on Las Vegas, 1972). In China streets are the real public space for people’s daily life and its essential activities (trading, eating, playing, discussing): their role in urban life is so strong that sometime a street can appear even where the planning didn’t establish that. The western main urban public/social space is the square, but for the eastern countries - especially China- the streets represent the most representative urban public space that can be used together without the class differences. However, from the ancient cities to today’s high-density cities, the Chinese streets, because of their social role, have experienced also a very important connection with shop signs, posters, notices of all kinds, flags and signs, luminous writings. All these objects are a kind of ornament of daily-life as well as a real interesting documentary material, useful to understand permanencies and variations in the use of the cities during their transition from the former order to the new one. The paper introduces the framework and the contents of a multidisciplinary research project at work, between urban morphology and Chinese language and culture. (max. 1500 characters, spaces included)